2020
DOI: 10.3390/toxins13010012
|View full text |Cite
|
Sign up to set email alerts
|

Cell Death Signaling Pathway Induced by Cholix Toxin, a Cytotoxin and eEF2 ADP-Ribosyltransferase Produced by Vibrio cholerae

Abstract: Pathogenic microorganisms produce various virulence factors, e.g., enzymes, cytotoxins, effectors, which trigger development of pathologies in infectious diseases. Cholera toxin (CT) produced by O1 and O139 serotypes of Vibrio cholerae (V. cholerae) is a major cytotoxin causing severe diarrhea. Cholix cytotoxin (Cholix) was identified as a novel eukaryotic elongation factor 2 (eEF2) adenosine-diphosphate (ADP)-ribosyltransferase produced mainly in non-O1/non-O139 V. cholerae. The function and role of Cholix in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 87 publications
(136 reference statements)
0
7
0
Order By: Relevance
“…Mitogen-activated protein kinases (MAPKs), represented by p38, JNK, and ERK1/2, are a common signaling pathway cascades in responding to extracellular stimulation. Since previous studies have shown that JNK phosphorylation is related with calcification in SMC, 16 , 17 we examined if nHAp activated JNK signaling pathway in SMCs. Significantly more phosphorylated JNK was detected after VSMCs were treated with nHAp for 15 min ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitogen-activated protein kinases (MAPKs), represented by p38, JNK, and ERK1/2, are a common signaling pathway cascades in responding to extracellular stimulation. Since previous studies have shown that JNK phosphorylation is related with calcification in SMC, 16 , 17 we examined if nHAp activated JNK signaling pathway in SMCs. Significantly more phosphorylated JNK was detected after VSMCs were treated with nHAp for 15 min ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…Other reports also show that nHAp can activate other MAPK members, like p38 and ERK1/2 pathways. 16 , 17 , 53 Whether they are also involved in the process of calcification caused by nHAp remains to be proved.…”
Section: Discussionmentioning
confidence: 99%
“…The cholera toxins, adnexa cholera toxin and closed band toxin produced by V. cholerae cause activation of anion secretion, inhibit absorption of electroneutral NaCl, destroy intestinal barrier function, and cause severe diarrhea (Ramamurthy et al, 2020). The serotypes O1 and O139 of V. cholerae strains with two main virulence genomes: cholera toxin (CT) and pathogenic toxin colonies cause an acute watery diarrhea (Ogura et al, 2020). A recent study showed that some non-01/O139 V. cholerae (NOVC) strains also cause diarrhea (Vezzulli et al, 2020).…”
Section: Bacteria and Diarrheamentioning
confidence: 99%
“…This clinical condition is histologically characterized as an aseptic coagulative necrosis, which consists of a massive destruction of skin structures without direct involvement of infectious agents [ 13 - 15 ]. This picture has a very intriguing mechanism, since the venom does not directly activate the leukocytes involved in the tissue destruction, but instead causes an initial activation of the endothelium, which in turn indirectly activates the leukocytes [ 16 , 17 ]. Signs like itching and skin rash in the vicinity of the bite site are also reported, which suggest an allergenic component in the venom [ 3 , 6 , 8 , 10 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are related to the uncontrolled activation of inflammatory response that appears after envenoming, which results in the skin injury, in addition to triggering the systemic deleterious processes previously mentioned. Herein, phospholipases D will not be explored, since updated data on them were extensively reviewed in recent publications [ 6 , 17 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%